INFLUÊNCIA DE DIFERENTES DIETAS NO DESENVOLVIMENTO DE LARVAS DE Musca Domestica (DIPTERA, MUSCIDAE) EM LABORATÓRIO - Chaves, L. E. L.; Casagrande, M. V.; Dias, F. H.; Kossoy, A.; Berti Filho, E. (REVISTA DE AGRICULTURA, 2015)
INFLUÊNCIA DE DIFERENTES DIETAS NO DESENVOLVIMENTO DE LARVAS DE Musca Domestica (DIPTERA, MUSCIDAE) EM LABORATÓRIO